Agglomeration and diffusion of urban functions: An approach based on urban land use conversion. (August 2016) - Zhou, Guolei; Li, Chenggu; Li, Moyin; Zhang, Jing; Liu, Yanjun
Abstract: The growth of urban space occurs not only through urban land expansion, but also from the conversion of urban development land. Urban land use conversion can reveal the inherent characteristics of the agglomeration and diffusion of urban functions. This paper presents the central city of Changchun as a case study. With the help of topographic and urban land use maps covering the years 2003, 2007, 2010, and 2013, the authors analyze the spatial patterns of four urban functions. The authors examine the conversion characteristics of residential, commercial, public service and industrial land. Urban land development and redevelopment are used to explain the spatial pattern of urban functions. The study identifies three concentric zones in Changchun based on the evolution of urban functions. In addition, our work also finds that urban planning lags behind urban development in less developed cities due to its rapid urban growth. Highlights: Urban land use conversion is active in the central city in less developed cities. Urban land use conversion includes development and redevelopment of urban land. Urban land use conversion is a new and effective way to study urban functions. Development and redevelopment of urban land can explain changes of urban function. Urban planning lags behind urban development in less developed cities.